Implementasi Sistem Pengelolaan Donasi, Kegiatan, dan Relawan Komunitas Sosial Turun Tangan Malang berbasis Web dengan Framework Codeigniter - Axel Iskandar; Agi Putra Kharisma; Sutrisno Sutrisno (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Turun Tangan Malang Community has various social activities, such as health socialization, teaching and learning activities to schools in need, fundraising for areas affected by disasters, skills training for rural communities, and so on. In a previous study by Muhammad Rifqi Ramadhani, research and information gathering on the Turun Tangan Malang community was carried out, and several problems were found, the first being the need for funds to carry out community activities. Furthermore, the limitations of human resources from each activity held. Data collection from volunteers is also not well coordinated and maximal. With these problems, the author wants to carry out the implementation process of system analysis and design that has been done by previous researchers, because the author wants to prove that the designs that have been carried out by the previous thesis can be implemented on a website-based application, and help the problems that exist in the Turun Tangan Malang community. In this thesis, the analysis and design process uses previous research as a reference and an interview process is carried out for data validation. For the implementation, the author uses the PHP programming language and the Codeigniter framework on the grounds that it can facilitate the author in implementing the system from the previous thesis design. The testing process is carried out using unit testing, integration, with the white-box testing method and validation using the black-box testing method, as well as compatibility testing which shows the system can run on various browsers.